A canvas model for risk assessment and performance estimation in public–private partnerships. Issue 6 (1st November 2020) - Kuru, Kadir; Artan, Deniz
Abstract: Public-private partnership (PPP) is being widely used to meet the growing infrastructure and service demand. However, previous literature draws attention to distressed or failed PPP projects due to significant risks. In the quest for assessing risks and estimating the performance at the outset of a project, there is a need for a practical tool allowing in-depth analysis of the project conditions. This paper aims to develop a PPP Canvas which enables assessment of the project risk factors and determining the related compensation mechanisms that can be used to mitigate these risks or allocate them to the parties in a balanced way. The Canvas also helps to estimate a project performance score based on the significance coefficients determined by the Analytical Hierarchy Process. AHP results show that stability of economic environment, political support and government intervention are the most important risk factors in the local context. AHP can be repeated for each specific PPP project, as part of the PPP Canvas process, to foster discussion and analysis of the risks and compensation mechanisms across different geographical locations and PPP project types. The paper adds a new dimension to PPP risk assessment by making use of the Business Model Canvas approach and the inclusion of contractual compensation and penalty mechanisms. As the stakeholders become more informed of the project conditions and the risks involved, they can make better decisions throughout the project life-cycle and can benefit from the identified compensation mechanisms in contract drafting.